Knowledge and Practices of Breastfeeding among Mothers in Mechinagar - Koirala, Rita; Paudel, Jiban Mani (Shahid Kirti Multidisciplinary Journal, 2023)
Although breastfeeding is a universal practice, it varies across social, economic, cultural, and educational variables in society. In this context, this paper explores knowledge and practices of breastfeeding among the mothers (N=132) in two culturally different groups, namely hill-origin and Tarai-origin, who live in Mechinagar, a village of the eastern Tarai of Nepal. This study was carried out based on mixed methods in which data were collected through Individual Survey (IS), Key Informant Interview (KII), and Focus Group Discussion (FGD). The findings of the study show that the knowledge of and behavior of breastfeeding among mothers are influenced and shaped by socio-demographic, cultural, and health-related factors, such as – caste and ethnic backgrounds, occupation, age, the birth interval between children, education, social belief, cultural values, etc. Consequently, the mother is not a homogeneous group, but rather a more diverse group that demands the concept of social heterogeneity for a better understanding of breastfeeding knowledge and behaviors in a diverse society. It will help to develop appropriate maternal educational programs to improve breastfeeding practices in society.